Pemanfaatan Limbah Fly Ash Sebagai Koagulan Dalam Pengolahan Air Melalui Ekstraksi Aluminium Dan Besi Menggunakan Metode Kalsinasi – Pengasaman - Malau, Alexander; Hendrawan, Ahmad; Albar, Azis; Lilih, Hendi; Ardiansah, Ardiansah (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2024)
The process of burning coal by PLTU produces large amounts of fly ash waste that has the potential to pollute the environment if not handled properly. Various kinds of research have been carried out to deal with fly ash waste, one of which is to make fly ash a coagulant material because it has a dominant aluminum and iron content. The conviction of the use of fly ash as a coagulant aims to determine the highest recovery presentation of aluminum and iron using HCl and H2SO4 solvents with variations in concentrations of 6%, 8%, and 10%, variations in extraction time of 2 hours, 4 hours, and 6 hours, and determine the rate of decrease in turbidity using the resulting coagulants. This study began with the preparation and characterization of fly ash samples using X-Ray Fluorescence (XRF), then the reparated sample mixed with Na2CO3 4 M is then calcined at a temperature of 950 ⁰C to be then extracted using HCl and H2SO4. The results showed that the highest percentage of extracted aluminum and iron recovery used 10% HCl for 6 hours ie 97.91% and 96.01%, and used 10% H2SO4% for 6 hours, 99.66% and 97.79%. Increasing solvent concentrations and extraction times cause increased concentrations of aluminum and extracted iron. Coagulant quality testing of fly ash using the jar test method, obtained the result that the coagulant results from the extraction of fly ash with HCl and H2SO4 solvents at 10% concentration% with an extraction time of 6 hours is the best coagulant that can reduce the value of turbidity to 0.61 NTU and 0.74 NTU.